A spear of summer grass [large type] - Raybourn, Deanna (Center Point Large Print, 2013)
Daughter of a scandalous mother, Delilah is already notorious even among Paris society. Her latest scandal is big enough to make even her oft-married mother blanch, and as a result Delilah is exiled to Kenya and her favorite stepfather's savanna manor house until the gossip subsides. The house is a sun-bleached skeleton of a faded dream in a decadent world full of expats. Then she meets Ryder White, her guide to the complex beauty of African wildlife and environments, and suddenly she discovers what is truly worth fighting for-- and what she can no longer live without.